Impericia Médica en Puerto Rico: 1990-1996 - Brau, Ricardo H.; Díaz, Clemente; Hawayek, José; Lojo, Juan J.; Malaret, Germán E.; Ramos-Barroso, Antonio; Rodríguez-Ortiz, Pablo (Puerto Rico Health Sciences Journal, 2016)
See manuscript